Binding Studies of AICAR and Human Serum Albumin by Spectroscopic, Theoretical, and Computational Methodologies - Shokoufeh Hashempour; Nahid Shahabadi; Aishat Adewoye; Brennen Murphy; Camaray Rouse; Brian A. Salvatore; Christopher Stratton; Elahe Mahdavian (Molecules, 2020)
The interactions of small molecule drugs with plasma serum albumin are important because of the influence of such interactions on the pharmacokinetics of these therapeutic agents. 5-Aminoimidazole-4-carboxamide ribonucleoside (AICAR) is one such drug candidate that has recently gained attention for its promising clinical applications as an anti-cancer agent. This study sheds light upon key aspects of AICAR’s pharmacokinetics, which are not well understood. We performed in-depth experimental and computational binding analyses of AICAR with human serum albumin (HSA) under simulated biochemical conditions, using ligand-dependent fluorescence sensitivity of HSA. This allowed us to characterize the strength and modes of binding, mechanism of fluorescence quenching, validation of FRET, and intermolecular interactions for the AICAR–HSA complexes. We determined that AICAR and HSA form two stable low-energy complexes, leading to conformational changes and quenching of protein fluorescence. Stern–Volmer analysis of the fluorescence data also revealed a collision-independent static mechanism for fluorescence quenching upon formation of the AICAR–HSA complex. Ligand-competitive displacement experiments, using known site-specific ligands for HSA’s binding sites (I, II, and III) suggest that AICAR is capable of binding to both HSA site I (warfarin binding site, subdomain IIA) and site II (flufenamic acid binding site, subdomain IIIA). Computational molecular docking experiments corroborated these site-competitive experiments, revealing key hydrogen bonding interactions involved in stabilization of both AICAR–HSA complexes, reaffirming that AICAR binds to both site I and site II.